Prospective 18 month surveillance study of MRSA colonization in an orthopedic unit in sri Lanka - V Thevanesam; H Suraweera; P Kannangara; IKB Weerasekera; HMW Abeywardena; EMW Ekanayake; TM Gamage; LVC Liyanapathirana (Sri Lankan Journal of Infectious Diseases, 2013)
The prevalence and acquisition of MRSA colonization at an Orthopaedic Unit in Sri Lanka were studied over an 18 month period. 260 of 1684 patients screened on admission were colonized with MRSA. Patients who were negative at preliminary screening were rescreened at weekly intervals during their hospital stay. Of 1424 patients who were rescreened, 170 acquired MRSA. This information is beneficial in planning and implementing suitable infection control procedures in Sri Lankan hospitals. <span lang="EN-GB" style="line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-ascii-theme-font: minor-latin; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi;"> <span lang="EN-GB" style="line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-ascii-theme-font: minor-latin; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi;">DOI: http://dx.doi.org/10.4038/sljid.v3i1.4046<span lang="EN-GB" style="line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-ascii-theme-font: minor-latin; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi;">